2013
DOI: 10.1371/journal.pone.0064724
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Antagonist Attenuates Lacrimal Gland, Lung, and Liver Fibrosis in a Murine Model of Chronic Graft-Versus-Host Disease

Abstract: Chronic graft-versus-host disease (cGVHD), a serious complication following allogeneic HSCT (hematopoietic stem cell transplantation), is characterized by systemic fibrosis. The tissue renin-angiotensin system (RAS) is involved in the fibrotic pathogenesis, and an angiotensin II type 1 receptor (AT1R) antagonist can attenuate fibrosis. Tissue RAS is present in the lacrimal gland, lung, and liver, and is known to be involved in the fibrotic pathogenesis of the lung and liver. This study aimed to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 46 publications
6
59
0
1
Order By: Relevance
“…Its features include skin fibrosis with increased collagen deposition, 29,31 pulmonary fibrosis, 31 inflammation and destruction of the salivary gland, 32 hepatic disease characterized by intrahepatic and extrahepatic bile duct mononuclear cell infiltration followed by fibrous thickening and sclerosis of the bile duct wall, 33,34 and lacrimal gland fibrosis. 35 We previously characterized the inflammatory and fibrotic changes in the lacrimal glands of B10.D2/BALB/c (H-2 d ) cGVHD mice. 35 Allogeneic transplantation, in which female BALB/c recipient mice received male B10.D2 donor bone marrow (1 · 10 6 /mouse) and spleen cells (2 · 10 6 /mouse), was used to generate the cGVHD model.…”
Section: Lacrimal Gland Fibrosis In a Murine Model Of Cgvhdmentioning
confidence: 99%
See 3 more Smart Citations
“…Its features include skin fibrosis with increased collagen deposition, 29,31 pulmonary fibrosis, 31 inflammation and destruction of the salivary gland, 32 hepatic disease characterized by intrahepatic and extrahepatic bile duct mononuclear cell infiltration followed by fibrous thickening and sclerosis of the bile duct wall, 33,34 and lacrimal gland fibrosis. 35 We previously characterized the inflammatory and fibrotic changes in the lacrimal glands of B10.D2/BALB/c (H-2 d ) cGVHD mice. 35 Allogeneic transplantation, in which female BALB/c recipient mice received male B10.D2 donor bone marrow (1 · 10 6 /mouse) and spleen cells (2 · 10 6 /mouse), was used to generate the cGVHD model.…”
Section: Lacrimal Gland Fibrosis In a Murine Model Of Cgvhdmentioning
confidence: 99%
“…35 We previously characterized the inflammatory and fibrotic changes in the lacrimal glands of B10.D2/BALB/c (H-2 d ) cGVHD mice. 35 Allogeneic transplantation, in which female BALB/c recipient mice received male B10.D2 donor bone marrow (1 · 10 6 /mouse) and spleen cells (2 · 10 6 /mouse), was used to generate the cGVHD model. For controls, syngeneic transplantation was used, in which female BALB/c recipient mice received male BALB/c donor bone marrow and spleen cells.…”
Section: Lacrimal Gland Fibrosis In a Murine Model Of Cgvhdmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also reported that macrophage infiltration and apoptosis in the kidney of fibrotic and cirrhotic rats [18, 19]. The pathological changes in extrahepatic organs, such as spleen, lung [20], and heart [21] associated with liver fibrosis have also been reported. However, the pathological changes in the intestine during the development of liver fibrosis were poorly understood.…”
Section: Discussionmentioning
confidence: 97%